Transcription factor specificity protein 1-mediated Serine/threonine kinase 39 upregulation promotes the proliferation, migration, invasion and epithelial–mesenchymal transition of hepatocellular carcinoma cells by activating the transforming growth factor-β1 /Smad2/3 pathway. Issue 1 (1st January 2021) - Wang, Jing; Fan, Zhenyu; Li, Jia; Yang, Jingmao; Liu, Xiaofei; Cheng, Jilin
ABSTRACT: Bioinformatics analysis showed that Serine/threonine kinase 39 (STK39), which was testified to play an important role in human cancers, may be a hub gene in diagnosing hepatocellular carcinoma (HCC). This study aimed to explore whether STK39 could be regulated by specificity protein 1 (SP1) to affect HCC cells malignant processes. Firstly, STK39 expression in tissues of HCC patients and several cell lines was analyzed. After STK39 silencing, cell proliferation was evaluated by methyl thiazolyl tetrazolium and colony formation assay. Tunel staining was used to detect cell apoptosis. Then, the abilities of cell migration and invasion were determined with wound healing and transwell assays. The expression of epithelial–mesenchymal transition (EMT)-related proteins and transforming growth factor-β1 (TGF-β1)/Smad2/3 pathway proteins was tested by western blot analysis. Thereafter, cells were overexpressed with SP1 under the circumstance of STK39 knockdown, and then the above cellular processes were under observation. Results revealed that the increased expression of STK39, which was found in both HHC patients and HCC cell lines, exhibited poor HCC prognosis. STK39 silencing inhibited Hep3b cell proliferation, migration, invasion, EMT and TGF-β1/Smad2/3 expression but promoted cell apoptosis. Additionally, SP1 could bind to the STK39 promoter and facilitate STK39 expression. Further studies revealed that the effects of STK39 silencing on Hep3b cells were blocked by SP1 overexpression. In conclusion, SP1-mediated STK39 up-regulation leads to the increased proliferation, migration, invasion and EMT of HCC cells via activating TGF-β1/Smad2/3 pathway. Therapies that target SP1 to knockdown STK39 expression may contribute to the inhibition of HCC progression. Graphical abstract: uf0001